An inoculant Bradyrhizobium strain with increased motility improves yield of soybean crops - Colla, Delfina; Brignoli, Damián; Iturralde, Esteban Tomás; Covelli, Julieta Mariana; Althabegoiti, María Julia; Perticari, Alejandro; Lodeiro, Aníbal Roberto (Asociación Argentina de Microbiología, 2023)
Poster y resumen